2012
DOI: 10.2131/jts.37.837
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth protects against arsenite-induced inhibition of proteoglycan synthesis in cultured vascular endothelial cells

Abstract: -Chronic ingestion of arsenic is associated with an increased risk of vascular disease such as atherosclerosis. Previously, we showed that arsenite inhibits the synthesis of general proteoglycans (PGs), which are key molecules in the progression of atherosclerosis, in vascular endothelial cells. In the present study, we investigated the effect of several metals on arsenite-induced inhibitory effect in endothelial cells. The results indicate that, after 24-hr incubation, the inhibition of PG synthesis caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We have previously shown that arsenite decreases the synthesis of both HSPGs and CS/DSPGs in cultured bovine aortic endothelial cells (Fujiwara et al, , 2012. Although the cells predominantly synthesize perlecan and biglycan (Saku and Furthmayr, 1989;Kaji et al, 2000), the PG type(s) of PGs, of which synthesis is inhibited by arsenite, has not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that arsenite decreases the synthesis of both HSPGs and CS/DSPGs in cultured bovine aortic endothelial cells (Fujiwara et al, , 2012. Although the cells predominantly synthesize perlecan and biglycan (Saku and Furthmayr, 1989;Kaji et al, 2000), the PG type(s) of PGs, of which synthesis is inhibited by arsenite, has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that arsenite, but not arsenate, decreases the synthesis of both HSPGs and CS/ DSPGs in cultured bovine aortic endothelial cells (Fujiwara et al, , 2012 using diethylaminoethyl-Sephacel column chromatography of radiolabeled PG molecules. However, type(s) of PGs of which synthesis is inhibited by arsenite is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In arterial smooth muscle cells, arsenite inhibited general proteoglycan synthesis, which might play a role of bias in the progression of atherosclerosis and vascular diseases [ 41 ]. In addition, this process is protected by the pretreatment of bismuth [ 42 ]. In the current study, we demonstrated that the relative length of protein-linked glycan residues may be dependent on the ATP in the model of arsenite-treated primary KC.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic role of Bi, as mentioned, has not been defined. Bi is an effective antidote for the adverse effects of As, mentioned above [20]. The protective role of Bi begins 24 hours after its administration.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%